Origins, function, and regulation of the TOC-TIC general protein import machinery of plastids - Richardson, Lynn G L (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.